A field-study on describing the Syriac manuscripts preserved in the depository of the O.A.O.C. - Samer Soreshow Yohanna; Qusay Yono Simaan Ajim (Zanco Journal of Humanity Sciences)
The Chaldean Antonian Order of St. Hormizd (O.A.O.C.) has always taken care of archival material and ancient books and manuscripts. Recently the Order gave an opportunity to the whole world to study these manuscripts and divulge them in the most modern ways and create a new place where local and western scholars can admire these treasures, thus they have established the Scriptorium Syriacum (S.S.) in Erbil to preserve these hundreds of precious manuscripts varying in topics: scripture, liturgy, canon law, history, philosophy, languages etc. These manuscripts amount today more than 2000 manuscripts ranging from the 9th century to recent years. This field-study comes after three previous attempts to catalogue this on-growing collection and present new data about the newly accessed manuscripts and to present a check-list of them as a contribution in discovering new Syriac texts.